The Dating and the Sequence of the Persid Frataraka Revisited - Müseler, Wilhelm (KOINON: The International Journal of Classical Numismatic Studies, 2018)
Archaeologists and in particular their nit-picking subspecies, the specialists of epigraphy or of numismatics, can be notorious fun-spoilers. Many scholars of ancient history have – at one point or another – undergone the rather frustrating experience that their inventive and frequently clever theories based mainly on their subjective interpretation of the textual evidence provided by the literary tradition are not compatible with the findings of epigraphic or numismatic research. Auxiliary constructions invented to circumnavigate this apparent dilemma tend to make the intended point even weaker the more elaborate they get. The few testimonies of the literary tradition have come upon us in a variously fractured and altered form: In most cases the principal information is transmitted here by late antiquity if not even medieval copies or excerpts of an original source lost a long time ago. They therefore leave open a rather wide space for all kinds of rational reconstructions and erudite opining about their original contents and meaning. In contrast to this type of evidence, epigraphic and numismatic remains have the characteristic quality of bearing direct and not subsequently edited, witness to circumstances and events at the time and place of their origin. Admittedly also coins and inscriptions leave space for various interpretations, but this is much more limited and the evidence provided by this type of source can hardly be contradicted in a forthright way.